Legal Regulation of the Synergetic effect of Innovation in the Structure of National E conomies of the Union State. / Regulación jurídica del efecto sinérgico de la innovación en la estructura de las economías nacionales del Estado de la Unión - Abramov, Ruslan A. ABRAMOV; Sokolov, Maksim S.; Surilov, Meir N.; Kochetkov, Evgeniy P. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT Assess of the constitutions of Russia and Belarus, to determine the degree of allowable discrepancy, to compare their laws, the realities of their application will be the science of constitutional law. The relevance of the research topic is that only in 2006 international treaties and agreements were concluded aimed at the settlement of the most pressing issues of ensuring equal rights of citizens of the Russian Federation and the Republic of Belarus in the field of social security, medical care, freedom of movement, choice of place of stay, as well as the regulation of property issues of the Union state. RESUMEN Se evalúan las Constituciones de Rusia y Belarús, para determinar el grado de discrepancia admisible, para comparar sus leyes, se aplicará a la realidad la ciencia del derecho constitucional. La importancia del tema de la investigación es que sólo en 2006 se celebraron tratados y acuerdos internacionales destinados a resolver las cuestiones más apremiantes de garantizar la igualdad de derechos de los ciudadanos de la Federación de Rusia y la República de Belarús en el ámbito de la seguridad social, la atención médica, la libertad de circulación, la elección del lugar de residencia, así como la regulación de las cuestiones de propiedad del estado de la Unión.